PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Made Galih Wisnu Wardana; Muhammad Ali Fikri (Jurnal Fokus Manajemen Bisnis, 2019)
This research aims to determine the effect of liquidity ratio (CR), solvency ratio (DER), profitability ratio (ROA), and activity ratio (TATO) on the Stock Price. The object that  is  used in this research are property and real estate sub sector companies listed in Indonesia Stock Exchange year 2015-2017. The population in this research is a whole of property and real estate sub sector companies listed in Indonesia Stock Exchange year 2015-2017 were 48 companies. The sampling technique is used purposive sampling with several criteria,  namely property and real estate sub sector companies listed in Indonesia Stock Exchange year 2015-2017, companies that submit financial reports during the research period, and companies that have positive net income report. The number of samples that fit the criteria were 34  companies. Data were analyzed by using data regression analysis with Eviews 6 software. The  results of this  research showed  that current  ratio, debt to equity ratio and total asset turn over are partially have positive and not have significant effect on the stock price, while return on assets have negative and not have significant effect on the stock price. Simultaneously that the current ratio, debt to equity ratio, return on assets and total asset turnover not have  significant effect on  the  stock price. R-square value of 0.019 indicates that the ability of the current ratio, debt to equity ratio, return on assets,  and  total  asset  turnover  while  explaining  the  Stock  Price  is  1.9%,  and  the 98.1% is explained by other variables which not contained in this research.